Da lógica manicomial às políticas de redução de danos : um estudo de caso sobre o CAPS-AD no estado de Mato Grosso - Barros, Alexandre Cesar de Amorim (2023)
Drug policies and the meanings regarding the production and consumption of narcotics have transformed over time according to the social imaginary of the time, principles, interests, subjectivities and the power/knowledge strategies established in each historical period. Over time, drug policies in Brazil have mobilized everything from repressive and disciplinary practices linked to the war on drugs and asylum logic, with the confinement of users and drug addicts, to harm reduction (RD) policies, with resocialization strategies that privilege the “freedom”, “self-care” and “autonomy” of individuals. Sociologically, this research is part of the study of the different treatments that drug policies have given to users and drug addicts, raising the following problem: to what extent drug policies and resocialization practices carried out by CAPS-AD are related to the set of transformations in the rationality and power strategies of contemporary capitalism? The objective of the research is to sociologically interpret harm reduction and CAPS-AD from the perspective of power and qualitatively circumscribe them between the power technologies of disciplinary societies and control societies, linked to the emerging neoliberal rationality. The methodological approach is qualitative, the design is a case study at CAPS-AD in the State of Mato Grosso; the resources and techniques used are documentary and bibliographical research, interviews and observation. It was carried out between a semi-structured individual interview with CAPS-AD professionals and the collection of documents regarding the demand for service and the profile of the clientele. We maintain that modern and contemporary technologies of power juxtapose, alternate and intertwine in the resocialization practices of CAPS AD, so that both the current drug policy, based on harm reduction, and modern asylum logic are articulated in the institution through discourses and practices. We thus demonstrate the manifestation of a hybrid power technology of individual conformation and mental health management.